Estudo das propriedades do óxido de nióbio a partir de uma perspectiva computacional - Ody, Kamila da Silva (2018)
Nanotechnology presents a breakthrough in the discovery and exploration of the physical and chemical properties of new emerging complex materials that are promising for numerous desired scientific and technological applications and, in addition, is a highly multidisciplinary field of research. In particular, the development of new complex nanomaterials has been the focus of numerous recent studies and presents a fascinating challenge. In recent times, niobium oxides, such as Nb2O5, are considered semiconductor materials with very attractive physical and chemical properties for applications in various areas, such as catalysis, sensors, medical, aerospace, etc. Especially, the characterization of Nb2O5 based nanostructures has received much attention in recent years, however, despite the great importance of this system some of its fundamental properties are still not well understood. In cases like this computational chemistry methods can contribute to a rationalization, this is one of the foundations presented by these enriched nanostructures, and consequently, it will lead new perspectives and ideas for its exploration and apply in different fields of nanotechnology. The objective of the present work is to use theoretical methodologies by means of DFT calculations using periodic models to investigate the physical and chemical properties of niobium nanostructures. Band structures, energy band gap and state density will be investigated in this study. From these tools it is possible to unravel the relationships between composition, structure, size, morphology and their properties, which may contribute to the future development of new devices and applications based on these materials.